2022
DOI: 10.3390/en15030866
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Concept of Hydrogen Supply Chains and Power Grids Powered by Renewable Energy Sources: A Scoping Review with the Use of Text Mining

Abstract: The key direction of political actions in the field of sustainable development of the energy sector and economy is the process of energy transformation (decarbonization) and increasing the share of renewable energy sources (RES) in the supply of primary energy. Regardless of the indisputable advantages, RES are referred to as unstable energy sources. A possible solution might be the development of the concept of hydrogen supply chains, especially the so-called green hydrogen obtained in the process of electrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Current research on hydrogen supply chains focusses on how hydrogen relates to influencing factors regarding management of electricity and distribution networks that fuel renewable energy sources (RES). The concept of designing a hydrogen supply chain that differentiates the phases of supply, production, storage, and distribution of electricity is needed [13].…”
Section: Hydrogen Energy Supply and Demand Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research on hydrogen supply chains focusses on how hydrogen relates to influencing factors regarding management of electricity and distribution networks that fuel renewable energy sources (RES). The concept of designing a hydrogen supply chain that differentiates the phases of supply, production, storage, and distribution of electricity is needed [13].…”
Section: Hydrogen Energy Supply and Demand Dynamicsmentioning
confidence: 99%
“…Their study also aimed to assess environmental performance parameters to establish correlations between renewable energy's environmental, economic, and energy use factors. The significance of links between ecological factors and energy use has also been emphasised using Spearman's correlation to identify indicators of energy sustainability measurement [10][11][12][13][14]. Ref [15] reported that a remote generator will save almost 90% of its total costs due to the decrease in the cost of hydrogen fuel by 2030.…”
Section: Introductionmentioning
confidence: 99%
“…The operation of many structures-particularly, steam and hydrogen turbine rotors, cooling infrastructures of powerful semiconductor devices and industrial singlecrystal growth applications [3][4][5][6][7][8][9][25][26][27][28][29][30][31][32][33][34]45,[55][56][57][58][59][79][80][81][82][83][84][85][86][87][88][89][90][91]110]-is accompanied by their cyclic loads, which often exceed the yield strength of the material [52,[54][55][56], based on understanding the hydrogen embrittlement of materials from the atomistic level to the continuum [100][101][102][103][123][124][125]…”
Section: Hydrogen Influence On the Welded Joint Durability Under Cycl...mentioning
confidence: 99%
“…RES technologies provide an excellent opportunity to mitigate greenhouse gas emissions and reduce global warming by replacing fossil fuels. Nevertheless, regardless of the indisputable advantages, RES is an unstable energy source due to the dependence of produced energy volume on non-controllable factors such as weather and time of day (Frankowska et al, 2022). The solution to these problems is the use of hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…A critical literature analysis proves that hydrogen supply chains are a complex and demanding research area (Frankowska et al, 2022). In the theoretical achievements, separate studies have mainly focused on individual phases of the functioning of hydrogen supply chains.…”
Section: Introductionmentioning
confidence: 99%